PENGARUH SERTIFIKAT HALAL TERHADAP PENINGKATAN PENDAPATAN PENJUALAN USAHA DI SEKTOR FOOD AND BEVERAGE KOTA MAKASSAR - Syamsuri Rahim; Tiara Halifah Puspa Sari; Nur Wahyuni (Jurnal Bisnis dan Kewirausahaan, 2023)
Halal products have become a world trend because they have a potential market. It has been recognized that halal has a very important economic value, awareness of the concept of halal began to increase, and many companies in the field of products and services began to respond to consumer needs. The purpose of this study was to determine the effect of halal certificates on increasing income. This type of research uses descriptive quantitative methods. The variables studied consisted of halal certificate (X) and increase of income (variable Y). The data sources used are primary and secondary. Data collection is distribute questionnaires to 30 food and beverage sector companies in Makassar. The results of the study with simple linear regression analysis method showed that the effect of halal certificates was 41.3% and the remaining 58.7% could be explained by other variables not explained in this study.